Comparison of characteristics and anti-MDA5 antibody distribution and effect between clinically amyopathic dermatomyositis and classic dermatomyositis: a retrospective case-control study - Ji, Qiang; Pan, Wenping; Zhang, Di; Hou, Yanfeng; Wang, Zhankui (Frontiers in Immunology, 2023)
Background: Clinically amyopathic dermatomyositis (CADM) is a distinct subtype of dermatomyositis (DM) characterized by typical DM cutaneous findings but with minimal or no evidence of myositis. It possesses unique features different from classic DM (CDM). Anti-melanoma differentiation-associated gene 5 (MDA5) antibodies were found in CADM and are thought to increase the risk of rapidly progressive interstitial lung disease (RP-ILD) and are present in both CADM and CDM patients, affecting their condition and prognosis. Nevertheless, no large-sample studies have compared all aspects concerning patients with CADM and those with CDM. This study aimed to investigate differences in clinical characteristics and risk factors for mortality between CADM and CDM and to clarify the distribution and impact of anti-MDA5 antibodies in patients with these conditions. Methods: A retrospective case-control study included 330 patients and collected and analyzed their clinical data from The First Affiliated Hospital of Shandong First Medical University and Shandong Provincial Hospital of Traditional Chinese Medicine between January 2015 and July 2022; all patients were followed up to evaluate changes in their condition and prognosis. Results: We found CADM to be associated with higher rates of mortality, 1-year mortality, interstitial lung disease (ILD), and RP-ILD than CDM. In CADM, RP-ILD, anti-MDA5 antibodies, and high ferritin and lactate dehydrogenase (LDH) levels were identified as independent risk factors for death. In CDM, the neutrophil-to-lymphocyte ratio, anti-MDA5 antibodies, and high ferritin levels were shown to be independent risk factors for death, whereas mechanic’s hand was considered a protective factor against it. Anti-MDA5 antibody-positive patients did not exhibit any significant difference based on whether they belonged to the CADM or CDM groups. When no anti-MDA5 antibody-positive patients participated, the ferritin levels and rates of RP-ILD and ILD were still higher in CADM than in CDM; however, such differences decreased, whereas the LDH levels, rates of mortality, and 1-year mortality did not differ. Anti-MDA5 antibody-positive patients consistently showed higher LDH and ferritin levels, lower lymphocyte levels, higher probability of RP-ILD and ILD, and worse prognosis than anti-MDA5 antibody-negative patients, irrespective of whether the patients had DM, CADM, or CDM.